Findbuch des Bestandes Abt. 13: Obergericht zu Gottorf 1713-1834 - Rathjen, Jörg (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2017)
Since the middle of the seventeenth century, the "Regierungskanzlei" (government chancellery )in Glückstadt was an authority under the auspices of the central authorities in Copenhagen. It performed important tasks of administration and legal administration in the royal territories of the Duchies of Schleswig andHolstein. The Supreme Court carried out supervision in administrativematters mainly in the areas of church, school, pauper police, economics anddyke. When the Judiciary and Administration were separated from each otherin 1834, the administrative responsibilities of the Supreme Court weretransferred to the newly formed Schleswig-Holstein government. Under thenew designation of "Schleswig´s Landdicasterien", the Supreme Court ofGottorf ("Gottorfer Obergericht") henceforth acted only as a pure judicialauthority which was subordinated to the Superior Court of Appeal in Kiel.The archival materials of the "Gottorfer Obergericht" as presented in thispublication were delivered by and by to the LandesarchivSchleswig-Holstein. The profound and modern edition of the archival Materials is mainly relevant for local research.The publication brings together the concordances 13A and 13B for the firsttime. The aim of this work is to facilitate access to and work with thearchival materials.